Only Minor Changes in the Soil Microbiome of a Sub-alpine Forest After 20 Years of Moderately Increased Nitrogen Loads - Frey, Beat; Carnol, Monique; Dharmarajah, Alexander; Brunner, Ivano; Schleppi, Patrick (Frontiers in Forests and Global Change, 2020)
Soil appears to play a key role in the response of the forest ecosystems to N deposition. Twenty years of experimental moderate N addition in a sub-alpine forest increased nitrate leaching, but the soil immobilized most of the N input, gradually decreasing the C:N ratio. Exchangeable and microbial N were only slightly affected, but denitrification and N2O production were increased and soil respiration tended to be reduced while soil microbial communities were remarkably resistent. It is assumed that these changes at the process level are related to the soil microbiome, but soil microbial communities have not been assessed so far at lower taxonomical resolution in this long-term experiment. The aim of this study is to understand the underlying causes of the results obtained so far by assessing how N treatment affects the soil microbiome at different soil depths. We analyzed bacterial and fungal diversity and community structures using Illumina MiSeq sequencing and quantified the responses of the N cycling communities to elevated N loads by quantitative PCR. The microbial functions were assessed by respiration, N mineralization and potential nitrification. Bacterial and fungal α-diversity, observed richness and Shannon diversity index, remained unchanged upon N addition. Multivariate statistics showed shifts in the structures of fungal but not bacterial communities with N load, while the changes were minor. Differences in the community compositions associated with the N treatment were mainly observed at a lower taxonomical level. We found several fungal OTUs in particular genera such as the ectomycorrhizal fungi Hydnum, Piloderma, Amanita and Tricholoma that decreased significantly with increased N-loads. We conclude that long-term moderate N addition at this forest site did not strongly affect the soil microbiome (which remained remarkably resistant) and its functioning.